Computing Substrate Selectivity in a Peptide Transporter. Issue 2 (18th February 2016) - Colas, Claire; Smith, David E.; Schlessinger, Avner
Abstract : The human proton-coupled peptide transporter 1 (PepT1) is responsible for the absorption of di- and tri-peptides from the diet and peptide-like drugs. In this issue of Cell Chemical Biology, Samsudin et al. (2016) use an integrated computational and experimental approach to provide new insights into understanding substrate selectivity of PepTSt, a prokaryotic homolog of the human PepT1. Abstract : The human proton-coupled peptide transporter 1 (PepT1) is responsible for the absorption of di- and tri-peptides from the diet and peptide-like drugs. In this issue of Cell Chemical Biology, Samsudin et al. (2016) use an integrated computational and experimental approach to provide new insights into understanding substrate selectivity of PepTSt, a prokaryotic homolog of the human PepT1.